Beliefs about Penis Size: Validation of a Scale for Men Ashamed about Their Penis Size. (1st January 2014) - Veale, David; Eshkevari, Ertimiss; Read, Julie; Miles, Sarah; Troglia, Andrea; Phillips, Rachael; Echeverria, Lina Maria Carmona; Fiorito, Chiara; Wylie, Kevan; Muir, Gordon
Abstract: Introduction: No measures are available for understanding beliefs in men who experience shame about the perceived size of their penis. Such a measure might be helpful for treatment planning, and measuring outcome after any psychological or physical intervention. Aim: Our aim was to validate a newly developed measure called the Beliefs about Penis Size Scale (BAPS). Method: One hundred seventy-three male participants completed a new questionnaire consisting of 18 items to be validated and developed into the BAPS, as well as various other standardized measures. A urologist also measured actual penis size. Main Outcome Measures: The BAPS was validated against six psychosexual self-report questionnaires as well as penile size measurements. Results: Exploratory factor analysis reduced the number of items in the BAPS from 18 to 10, which was best explained by one factor. The 10-item BAPS had good internal consistency and correlated significantly with measures of depression, anxiety, body image quality of life, social anxiety, erectile function, overall satisfaction, and the importance attached to penis size. The BAPS was not found to correlate with actual penis size. It was able to discriminate between those who had concerns or were dissatisfied about their penis size and those who were not. Conclusions: This is the first study to develop a scale for measurement of beliefs about penis size. It may be used as part of an assessment for men who experience shame about the perceived size of their penis and as an outcome measure after treatment. The BAPS measures various manifestations of masculinity and shame about their perceived penis size including internal self-evaluative beliefs; negative evaluation by others; anticipated consequences of a perceived small penis, and extreme self-consciousness.